Human eyetracking reveals a general avoidance of spider images but a bias toward spider-specific features - Brase, Emma C.; Hebets, Eileen A.; Smith, Kevin B.; Pessman, Brandi; Akin, Heather; Boutard, Harley M.; Hernández, Laura Segura; Hedin, Marshal; Dodd, Michael D. (Frontiers in Arachnid Science, 2026)
Many people are afraid of spiders and consider them to be both dangerous and disgusting, which can negatively impact their mental well-being as well as their relationship with nature. Very few studies have examined what characteristics draw visual attention toward or away from spiders, or have assessed the impact of arachnophobia and sex on attentional biases. Here, 118 undergraduate students freely viewed single and paired images of spiders and other arthropods in their natural environments while having their eye movements monitored. Participants also completed a survey measuring spider phobia and attitudes toward spiders. Multiple eyetracking metrics (total dwell time, first run dwell time, first fixation time, and run count) were used as indicators of attentional bias. Findings suggest a general avoidance of spider images in the presence of other non-spider arthropod images as well as avoidance of scorpion images in the presence of non-scorpion arachnid images. Presentation of image pairs with two kinds of spiders elicit attention toward spider-specific features. These effects were occasionally, though not often, moderated by sex and phobia levels. Across all metrics, there was a tendency to record longer first fixation times, shorter dwell times, and lesser run counts toward images of spiders. Images of jumping spiders and insects received considerably more and faster attentional allocation relative to other spiders. Understanding how general body form versus specific spider features influence visual attention provides insight into visual factors that may motivate spider phobia, providing evidence-based knowledge that could be useful in treatments. Additionally, knowledge of potentially appealing features of spiders may provide useful perspectives for communicating the usefulness of spiders in our ecosystem.